TRANSFORMASI DIGITAL UMKM: KAJIAN LITERATUR KESIAPAN ADOPSI CLOUD ACCOUNTING DI ERA DIGITALISASI (A Systematic Literature Review) - Firdaus, Nurwahidah; Septiandi, Indra Dwi Cahya; Anggraeni, Naufa Julia; Purnamasari, Wulan (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2025)
Digital transformation has become an urgent necessity for Micro, Small and Medium Enterprises (MSMEs) to remain competitive in the modern era. However, the adoption of cloud-based accounting technology still faces various challenges. The objective of this research is to identify key factors influencing cloud accounting adoption among MSMEs. The methodology employed is a systematic literature review using to analyze technology, organization, environment and individual factors affecting adoption. The research findings indicate that technology factors such as ease of use and data security, organizational factors including management support and resources and environmental factors like competition and regulation significantly influence cloud accounting adoption decisions. This research contributes guidance for academics and practitioners in understanding MSME digital transformation dynamics and assists governments in formulating more effective policies to support technology adoption